Influence of orthostatic loading probes on pumping function of the heart of athletes with disabilities of health - Vakhitov, L.I. (2019)
In the present research, the reaction of the pumping function of the heart (PFH) of disabled athletes to an orthostatic test was studied. Analysis of indicators of the pumping function of the heart was carried out in two stages. At the first stage, the PFH indicators of disabled athletes in the prone position were investigated. In the second stage, the urgent reaction of the indicators of the pumping function of wheelchair basketball players was carried out for 5–20 seconds after an active transition from a prone position to a sitting position. It was revealed that in wheelchair basketball players with amputated lower limbs, the difference in heart rate parameters during an orthostatic test was significantly higher than in basketball players with atrophy of the lower limbs. Basketball players with amputated lower limbs react to large changes in body position with active changes in body position than athletes with atrophied lower limbs.